Efficacy of a Bolus Dose of Esmolol and Bolus Dose of Lignocaine for Attenuating the Pressor Response to Laryngoscopy and Endotracheal Intubation in General Anesthesia: A Comparative Study - Mulimani, Sridevi Mallanna (Anesth Essays Res, 2019)
CONTEXT: Laryngoscopy and endotracheal intubation result in an increase in heart rate and blood pressure; they evoke life-threatening complications. The esmolol is short-acting cardioselective beta-blocker and brings advantages to the perioperative management of tachycardia and hypertension. AIMS: The aim of this study was to compare the efficacy of a bolus dose of esmolol and bolus dose of lignocaine for attenuation of the pressor response to laryngoscopy and intubation. SETTINGS AND DESIGN: Sixty patients of both sex, aged 20–50 years, belonging to the American Society of Anesthesiologists physical Status I and II randomly allocated into two groups (n = 30). MATERIALS AND METHODS: The study drugs diluted in 10-ml normal saline. Group I received esmolol 1.5 mg/kg and Group II received lignocaine 1.5 mg/kg 2 min before inducing the patients with thiopentone 5 mg/kg and suxamethonium 1.5 mg/kg. The heart rate, systolic blood pressure, and diastolic blood pressure were measured at basal, during intubation, and 1, 2, 3, and 5 min after intubation, and based on these values, the mean arterial pressure (MAP) and rate pressure product (RPP) was calculated. STATISTICAL ANALYSIS USED: The Student's t-test and data were represented by mean standard deviation and graphs. RESULTS: The mean pulse rate, mean of MAP, and mean of RPP at intubation and at 1, 2, 3, and 5 min after intubation in lignocaine group showed a significant rise in these values but in esmolol group it remained nearer to or less than baseline values. CONCLUSIONS: Esmolol 1.5 mg/kg is effective in attenuating the pressor response in comparison with lignocaine 1.5 mg/kg during laryngoscopy and intubation.